Post-traumatic stress disorder symptoms after acute lung injury: a 2-year prospective longitudinal study. Issue 12 (December 2013) - Bienvenu, O. J.; Gellar, J.; Althouse, B. M.; Colantuoni, E.; Sricharoenchai, T.; Mendez-Tellez, P. A.; Shanholtz, C.; Dennison, C. R.; Pronovost, P. J.; Needham, D. M.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Survivors of critical illnesses often have clinically significant post-traumatic stress disorder (PTSD) symptoms. This study describes the 2-year prevalence and duration of PTSD symptoms after acute lung injury (ALI), and examines patient baseline and critical illness/intensive care-related risk factors. Method This prospective, longitudinal cohort study recruited patients from 13 intensive care units (ICUs) in four hospitals, with follow-up 3, 6, 12 and 24 months after ALI onset. The outcome of interest was an Impact of Events Scale – Revised (IES-R) mean score ⩾1.6 ('PTSD symptoms'). Results During the 2-year follow-up, 66/186 patients (35%) had PTSD symptoms, with the greatest prevalence by the 3-month follow-up. Fifty-six patients with post-ALI PTSD symptoms survived to the 24-month follow-up, and 35 (62%) of these had PTSD symptoms at the 24-month follow-up; 50% had taken psychiatric medications and 40% had seen a psychiatrist since hospital discharge. Risk/protective factors for PTSD symptoms were pre-ALI depression [hazard odds ratio (OR) 1.96, 95% confidence interval (CI) 1.06–3.64], ICU length of stay (for a doubling of days, OR 1.39, 95% CI 1.06–1.83), proportion of ICU days with sepsis (per decile, OR 1.08, 95% CI 1.00–1.16), high ICU opiate doses (mean morphine equivalent ⩾100 mg/day, OR 2.13, 95% CI 1.02–4.42) and proportion of ICU days on opiates (per decile, OR 0.83, 95% CI 0.74–0.94) or corticosteroids (per decile, OR 0.91, 95% CI 0.84–0.99). Conclusions PTSD symptoms are common, long-lasting and associated with psychiatric treatment during the first 2 years after ALI. Risk factors include pre-ALI depression, durations of stay and sepsis in the ICU, and administration of high-dose opiates in the ICU. Protective factors include durations of opiate and corticosteroid administration in the ICU.